Ethics of War and Ethics in War - Babic, Jovan (Conatus - Journal of Philosophy, 2019)
The paper examines the justification of warfare. The main thesis is that war is very difficult to justify, and justification by invoking “justice” is not the way to succeed it. Justification and justness (“justice”) are very different venues: while the first attempts to explain the nature of war and offer possible schemes of resolution (through adequate definitions), the second aims to endorse a specific type of warfare as correct and hence allowed – which is the crucial part of “just war theory.” However, “just war theory,” somewhat Manichean in its nature, has very deep flaws. Its final result is criminalization of war, which reduces warfare to police action, and finally implies a very strange proviso that one side has a right to win. All that endangers the distinction between ius ad bellum and ius in bello, and destroys the collective character of warfare (reducing it to an incomprehensible individual level, as if a group of people entered a battle in hopes of finding another group of people willing to respond). Justification of war is actually quite different – it starts from the definition of war as a kind of conflict which cannot be solved peacefully, but for which there is mutual understanding that it cannot remain unresolved. The aim of war is not justice, but peace, i.e. either a new articulation of peace, or a restoration of the status quo ante. Additionally, unlike police actions, the result of war cannot be known or assumed in advance, giving war its main feature: the lack of control over the future. Control over the future, predictability (obtained through laws), is a feature of peace. This might imply that war is a consequence of failed peace, or inability to maintain peace. The explanation of this inability (which could simply be incompetence, or because peace, as a specific articulation of distribution of social power, is not tenable anymore) forms the justification of war. Justice is always an important part of it, but justification cannot be reduced to it. The logic contained here refers to ius ad bellum, while ius in bello is relative to various parameters of sensitivity prevalent in a particular time (and expressed in customary and legal rules of warfare), with the purpose to make warfare more humane and less expensive.